(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Introduction: Heart failure is a serious and costly condition. Health expenditures related to heart failure continue to increase. In Madagascar, the failure of the social and health insurance system prompted us to estimate these expenses in order to assess the impact on patients’ financial status. The objective of our study was to evaluate the direct costs of managing heart failure. Methodology: This was a cross-sectional descriptive study in the Intensive Cardiological Care Unit of the Befelatanana Teaching Hospital from February to April 2019. All patients admitted for heart failure who responded to the questionnaires were included. Patients with incomplete records or who have filed out against medical decision have been excluded. Results: Thirty cases were selected. Mean age was 52.33 +/- 17.11 years with a gender-ratio was 1. Average cost of hospitalization was 1, 536, 066,66 Ariary for an average hospital stay of 14.96 +/- 12.28 days. This cost represented 9.8 times the Malagasy Guaranteed Minimum Interprofessional Salary. The breakdown of this cost is as follows: pharmaceutical costs and consumables: 39.06%, fees for acts and additional examinations: 31.27%; living expenses: 20.15%; expenses for accompanying persons: 5.58%. More than 80% were the responsibility of accompanying persons and/or families. Conclusion: Heart failure is a condition that is very expensive in Madagascar. It is essential to have a good health insurance system and focus on prevention.